The selection paradox: selecting and evaluating trainee psychologists in the context of narrative theory - Kaschula, Joanne (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
Psychology has become an increasingly popular discipline for study in the South African context, with the number of students enrolling for courses increasing rapidly. The selection and evaluation of trainee psychologists is a complex and contested issue. With so few students reaching Masters level and the changing needs of the South African context, it becomes imperative that only the most suitable candidates are selected for entry into the field of professional psychology. This study focuses on the selection process of trainee psychologists at an institution that incorporates the narrative philosophy in both the selection and training of candidates. The question is raised, whether it is possible to utilize narrative principles in a process that is intended to judge and evaluate candidates? This presents a paradox. The paradox is illuminated in both the intentions behind the narrative questions in the application form and in the candidates' experiences of responding to these. The conclusion reached is that the narrative philosophy makes for an enriching and creative experience of the selection process for candidates but this however, does not ameliorate the negative effects of evaluation and the 'gaze'.
Keywords: Psychologists -- Training of -- South Africa; Psychology -- Study and teaching -- South Africa; Psychologists -- Selection and appointment -- South Africa